Biotribology of the ageing skin—Why we should care. (March 2019) - Limbert, Georges; Masen, Marc A.; Pond, Damien; Graham, Helen K.; Sherratt, Michael J.; Jobanputra, Rikeen; McBride, Andrew
Abstract: Ageing of populations has emerged as one of the most pressing societal, economic and healthcare challenges currently facing most nations across the globe. The ageing process itself results in degradation of physiological functions and biophysical properties of organs and tissues, and more particularly those of the skin. Moreover, in both developed and emerging economies, population ageing parallels concerning increases in lifestyle-associated conditions such as Type 2 diabetes, obesity and skin cancers. When considered together, these demographic trends call for even greater urgency to find clinical and engineering solutions for the numerous age-related deficits in skin function. From a tribological perspective, detrimental alterations of skin biophysical properties with age have fundamental consequences on how one interacts with the body's inner and outer environments. This stems from the fact that, besides being the largest organ of the human body, and also nearly covering its entirety, the skin is a multifunctional interface which mediates these interactions. The aim of this paper is to present a focused review to discuss some of the consequences of skin ageing from the viewpoint of biotribology, and their implications on health, well-being and human activities. Current and future research questions/challenges associated with biotribology of the ageing skin are outlined. They provide the background and motivation for identifying future lines of research that could be taken up by the biotribology and biophysics communities.